Seventh graders' perceptions of physical education courses - Mustafa Koc; İbrahim Sahın (Selcuk University, 2018)
AbstractThis study aims at determining eighth graders' views and thoughts of physical education courses in primary education schools through metaphors. The study group was composed of 58 students attending Altınşehir Primary Education school located in Adıyaman in the 2014-2015 academic year.The data were collected by asking each student to complete the sentence "physical education course is  like....... because ..........". In consequence, 24 metaphors created by 58 students were divided into four different categories - namely, (i) social development, (ii) physical development, (iii) psychological development, and (iv) mental development. The majority of the students (98.28%) were found to have created positive metaphors for the course while only 1.72% of them were found to have created negative metaphors.